The antimicrobial activity of essential oil from Dracocephalum foetidum against pathogenic microorganisms - Lee, Saet Byoul; Cha, Kwang Hyun; Kim, Su Nam; Altantsetseg, Shataryn; Shatar, Sanduin; Sarangerel, Oidovsambuu; Nho, Chu Won (MICROBIOLOGICAL SOCIETY KOREA, 2007)
A number of essential oils from Mongolian aromatic plants are claimed to have antimicrobial activities. The essential oil of Dracocephalum foetidum, a popular essential oil used in Mongolian traditional medicine, was examined for its antimicrobial activity. Eight human pathogenic microorganisms including B. subtilis, S. aureus, M. lutens, E. hirae, S. mutans, E. coli, C. albicans, and S. cerevisiae were examined. The essential oil of Dracocephaluni foetidum exhibited strong antimicrobial activity against most of the pathogenic bacteria and yeast strains that were tested; by both the agar diffusion method and the minimum inhibitory concentration (MIC) assay (MIC range was 26-2592 mu g/ml). Interestingly, Dracocephalum foetidum even showed antimicrobial activity against methicilin-resistant Staphylococcus aureus (MRSA) strains. We also analyzed the chemical composition of the oil by GC-MS and identified several major components, including n-Mentha-1,8-dien-10-al, limonene, geranial, and neral.
Keywords: RESISTANT STAPHYLOCOCCUS-AUREUS; ANTIBACTERIAL ACTIVITY; CHEMICAL-COMPOSITION; MECHANISMS; MEMBRANE; PLANTS